Performance of okra (Abelmoschus esculentus) to different irrigation levels and mulches under drip irrigation system - CHANGADE, NITIN M; SHARMA, VIKAS; KUMAR, RAJ (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out at Lovely Professional university, Phagwara, Punjab during 2019 to study the performance of okra under irrigation levels and mulching methods under drip irrigation. The treatment comprised of 3 irrigation levels (1.0 ETc, 0.8 ETc and 0.6 ETc) and 5 mulch methods (black plastic mulch, silver plastic mulch, straw mulch, soil mulch and no mulch) laid out in split plot design replicated thrice. The growth and yield attributes were significantly influenced by irrigation levels and mulching methods. The irrigation level I2 (0.8 ETc) significantly exhibited maximum plant height (100.45 cm), number of branches per plant (1.77), and yield per plant (216.59 g) whereas irrigation level I1 (1.0 ETc) recorded maximum pod yield (15.59 tonnes/ha) which is at par with irrigation level I2 (15.36 tonnes/ha). The black plastic mulch was found significantly superior over no mulch treatments in terms plant height, number of branches, pod yield per plant, pod yield (19.09 tonnes/ha). The maximum water use efficiency (0.41 tonnes/ha-cm) was recorded in irrigation treatment I3 and in black plastic mulch (0.46 tonnes/ha-cm). The interaction effect of irrigation and mulching not showed significant difference on pod yield but significantly affected water use efficiency. At interaction effect, the maximum water use efficiency (0.56 tonnes/ha-cm) in combination of I3 and M1. Maximum B:C ratio was recorded in irrigation level I1 (3.49) which is at par with I2 (3.40). Black plastic mulch recorded higher B:C ratio (3.40). The interaction effect did not showed significant effect on B:C ratio. Looking the higher yield of crop, water use efficiency and higher B:C ratio, it can be recommended that okra crop showed good performance under irrigation level I2 and black plastic mulch.